ANALISIS SISTEM PENGENDALIAN PERSEDIAAN OBAT-OBATAN PADA PUSKESMAS SEPAUK KABUPATEN SINTANG - Aulia, Resti; Sari, Wilda; Dwi Widyastuti, Reni; Fakhrul Yahya, Rizky (Jurnal Akuntansi, Auditing dan Investasi, 2024)
The supply of medicines is one of the important factors influencing the quality of services at a Puskesmas. Withoutsupplies in the Puskesmas, there will be a risk that it will not be able to meet the needs of using Puskesmas services,especially patients at the Sepauk Puskesmas. This research aims to determine the control of medicine supplies atthe Sepauk Health Center, Sintang Regency. By using a qualitative descriptive research method and the dataanalysis technique used is Flowchart system analysis to analyze and draw conclusions and answers to the InternalControl Questionnaire. Based on the results of this research, it shows that, in the Flowchart analysis, there arestill obstacles, namely in the system of supply and use of medicines. This problem occurs due to discrepancies ifthe quantity of medicine that arrives does not match the initial request, and there are medicines whose physicalcondition is damaged so they cannot be used at the Sepauk Health Center. The results of drug supply control atthe Sepauk Community Health Center in the control environment show that the control environment at the SepaukCommunity Health Center is very adequate, this is proven by the existence of regulations and policies,organizational structure, separation of duties and responsibilities, regular audits of drug management and alsothe existence of adequate training programs. And for the risk assessment, the Sepauk Community Health Centerhas also shown that it complies with applicable procedures, whereas the control activities themselves are notadequate because the Sepauk Community Health Center was found to have no restrictions on access to the database.